2022
DOI: 10.1155/2022/3790721
|View full text |Cite
|
Sign up to set email alerts
|

The Role of NLRP3 Inflammasome in Diabetic Cardiomyopathy and Its Therapeutic Implications

Abstract: Diabetic cardiomyopathy (DCM) is a serious complication of diabetes mellitus (DM). However, the precise molecular mechanisms remain largely unclear, and it is still a challenging disease to diagnose and treat. The nucleotide-binding oligomerization domain and leucine-rich repeat pyrin 3 domain (NLRP3) inflammasome is a critical part of the innate immune system in the host to defend against endogenous danger and pathogenic microbial infections. Dysregulated NLRP3 inflammasome activation results in the overprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 187 publications
(184 reference statements)
0
10
0
Order By: Relevance
“…In the meantime, the inflammatory response is another crucial sign of DN, and the NLRP3 inflammasome is crucial to the DN pathogenesis [40,41], persistent HG conditions can enable the NLRP3 inflammasome [42,43]. Therefore, treatment of DN can be achieved by inhibiting NLRP3 inflammasome.…”
Section: Discussionmentioning
confidence: 99%
“…In the meantime, the inflammatory response is another crucial sign of DN, and the NLRP3 inflammasome is crucial to the DN pathogenesis [40,41], persistent HG conditions can enable the NLRP3 inflammasome [42,43]. Therefore, treatment of DN can be achieved by inhibiting NLRP3 inflammasome.…”
Section: Discussionmentioning
confidence: 99%
“…While recent articles have provided valuable insights into the role of NLRP3 inflammasome in cardiomyopathy, several areas remain to be explored. Further research is required to clarify the upstream triggers and signaling pathways regulating activation of NLRP3 inflammasome in various types of cardiomyopathies 85 . Furthermore, more investigations are warranted to evaluate the clinical efficacy and safety of pharmacological agents targeting NLRP3 inflammasome in human patients (Table 2).…”
Section: Nlrp3 Inflammasome and Cardiomyopathiesmentioning
confidence: 99%
“…The involvement of the NLRP3 inflammasome and ncRNAs has been suggested in the development of cardiomyopathies, and these findings may have significant implications for diagnostic and prognostic purposes. As an illustration, the upregulation of NLRP3, ASC, caspase‐1, and IL‐1β is observed in a model of type 2 diabetes induced by streptozotocin (STZ) in conjunction with a high‐fat diet 85 . Moreover, it has been demonstrated that the activation of the NLRP3 inflammasome contributes to the development of cardiomyopathies and atrial fibrillation 126 .…”
Section: Potential Of Targeting Ncrnas Related To Nlrp3 Inflammasomementioning
confidence: 99%
See 2 more Smart Citations